1996
DOI: 10.1091/mbc.7.8.1209
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of focal adhesion kinase (FAK) signaling in focal adhesions decreases cell motility and proliferation.

Abstract: It has been proposed that the focal adhesion kinase (FAK) mediates focal adhesion formation through tyrosine phosphorylation during cell adhesion. We investigated the role of FAK in focal adhesion structure and function. Loading cells with a glutathione-S-transferase fusion protein (GST-Cterm) containing the FAK focal adhesion targeting sequence, but not the kinase domain, decreased the association of endogenous FAK with focal adhesions. This displacement of endogenous FAK in both BALB/c 3T3 cells and human um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
383
4
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 476 publications
(420 citation statements)
references
References 79 publications
(92 reference statements)
32
383
4
1
Order By: Relevance
“…ECM: Extracellular matrix, RGD: Arg-Gly-Asp, JNK: Jun Kinase migrate less e ciently than control cells (Ilic et al, 1995). The observation that overexpression of FAK increases cell migration while a dominant negative form of the kinase inhibits it are also consistent with a role for this kinase in dynamic regulation of focal adhesions during cell migration (Cary et al, 1996;Gilmore and Romer, 1996).…”
Section: Focal Adhesion Kinasesupporting
confidence: 73%
“…ECM: Extracellular matrix, RGD: Arg-Gly-Asp, JNK: Jun Kinase migrate less e ciently than control cells (Ilic et al, 1995). The observation that overexpression of FAK increases cell migration while a dominant negative form of the kinase inhibits it are also consistent with a role for this kinase in dynamic regulation of focal adhesions during cell migration (Cary et al, 1996;Gilmore and Romer, 1996).…”
Section: Focal Adhesion Kinasesupporting
confidence: 73%
“…In support of this hypothesis, treatment of fibroblasts with tyrosine kinase inhibitors blocks integrin-stimulated focal adhesion and stress fibre formation [15,22]. However, in contrast with this finding, it has been recently reported that FAK activity might play a more important role in cell migration than in focal adhesion assembly [23].…”
Section: Introductionmentioning
confidence: 92%
“…GST-fusion proteins were expressed and purified from Escherichia coli onto glutathione agarose as previously described (Gilmore and Romer, 1996). Transiently transfected cells were lysed in NET buffer and incubated with 40 ÎŒl (50 % slurry) of the purified GST-fusion protein-coated glutathione-agarose (4°C/2 hours).…”
Section: Gst Fusion Proteins Pull Down Assaysmentioning
confidence: 99%